Pragmatic Acts in Alms Begging in Lagos State, Nigeria (2012)
Previous studies on alms begging in the fields of medicine, psychology, sociology, journalism, and discourse analysis have depicted the phenomenon as a simple activity of requesting by indigent individuals who were often viewed as linguistically deficient. These studies did not adequately account for the context-driven and implicit communicative acts performed by beggars, thus limiting the understanding of this pragmatic phenomenon in society. Therefore, this study examined alms begging in Lagos state with a view to describing its distinctive pragmatic acts and implications. The study applied a modified version of Pragmatic Act theory, which is suitable for describing and interpreting speeches and communicative behaviours in naturally occurring conversational interactions. Using the observation method, speeches and other communicative behaviours of 100 purposively selected beggars were collected from 4 types of locations (public institutions, venues of social events, vehicle stations, and on the streets) in all the 20 local government areas of Lagos State by tape recording and note taking, in order to have a balanced representation of various types of begging behaviours. The data were subjected to pragmatic analysis. Discourse Conditioning Acts (DCAs) and Purpose Execution Acts (PEAs) are the two distinctive but intertwined pragmatic acts found in alms begging. Discourse Conditioning Acts were executed verbally (indirect speech acts) and non-verbally (psychological and physical acts). Beggars‘ indirect speech acts comprised arguing (attention-seeking, affinity negotiating, claiming, denying, complaining, protesting, questioning and threatening), use of politeness (tact, positivism, quietism, and sympathy) and appropriation of idioms. Beggars‘ psychological acts manifested as strategies of mood variation (weeping, sobbing, hissing and laughing), while their physical acts consisted of the strategies of body moves (posing, gazing, beckoning, nodding, bowing, waving and dancing). Both the psychological and the physical acts were extra-linguistic behaviours which beggars used to reinforce their verbal acts in order to emphasise their goal-driven, situation-constrained desperation. Beggars used DCAs to set-up and co-opt others, thereby compelling their target to give alms. Purpose Execution Acts used in obtaining alms, were direct acts, which included three types of direct speech acts (expressives, commissives and directives) together with their corresponding features of (telling, promising and requesting respectively). On the streets, beggars were inclined to use more PEAs than DCAs but in the other types of begging locations (public institutions, venues of social events, and vehicle stations) they use more DCAs than PEAs because of temporal and spatial contextual advantages. While beggars in Lagos state rely on Discourse conditioning acts to set-up and to co-opt potential alms givers, they employ Purpose execution acts to obtain alms from their targets. Thus, begging in the state is a complex, skilled activity which exhibits a considerable level of beggars‘ pragmatic competence. A comparative pragmatic study of alms begging in the Northern and Southern regions of Nigeria is expected to reveal more pragmatic acts performed by beggars.